2013
DOI: 10.1159/000346796
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Promote Hepatic Regeneration after Partial Hepatectomy in Rats

Abstract: Objectives: Our goal was to study the ability of mesenchymal stem cells (MSCs) to stimulate liver regeneration after partial hepatectomy in rats. Methods: MSCs were isolated from bone marrow and cultured in vitro. Their characteristics were analyzed by flow cytometry. After 70% partial hepatectomy, Sprague-Dawley rats were randomly divided into three groups: a control group that was injected with saline, animals that received bone marrow-derived MSCs (BM-MSCs) by tail vein injection (the BM-MSC-TV group) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 65 publications
5
30
0
Order By: Relevance
“…Thus, they may be ideal seed cells for the treatment of injured tissue. The use of BM-MSCs is also being explored in the fields of regenerative medicine and tissue engineering (Table 3) [20]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, they may be ideal seed cells for the treatment of injured tissue. The use of BM-MSCs is also being explored in the fields of regenerative medicine and tissue engineering (Table 3) [20]. …”
Section: Resultsmentioning
confidence: 99%
“…From these studies, in five, authors performed ADSCs transplantation [14, 1719, 21], whereas, in two, authors transplanted BM-MSCs [16, 20] (Table 1). In all included papers on MSCs transplantation following PH, authors used rats as experiment animals, except from the study of Saito et al [19], in which authors have performed their experiments in mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdel Aziz et al showed that bone marrow (BM) mesenchymal stem cells (MSCs) could differentiate into hepatocytelike cells and reduced fibrosis by decreasing the precipitation of collagen [6]. Li et al have found that MSCs promote hepatic regeneration after partial hepatectomy and there was no positive correlation between liver regeneration and the amount of homing of these BM-MSCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of reparative processes in the damaged liver under the effect of transplanted MSC has been demonstrated not once [10]. This effect can be mediated by several mechanisms.…”
mentioning
confidence: 99%